Generalized (α,β) order based on some growth properties of wronskians - T. Biswas; C. Biswas (Математичні Студії)
In this paper the comparative growth properties of composition of entire and meromorphic functions on the basis of their generalized (α,β) order and generalized lower (α,β) order of Wronskians generated by entire and meromorphic functions have been investigated.